A New Climate vulnerability Index Sistan and Baluchistan province - esmaeail ahmadi; zahra hejazizadeh; bohlol alijani; Mohammad saligheh; Hassan danaie fard (تحقیقات کاربردی علوم جغرافیایی)
The more exposure to Climate change / variability, the more vulnerability and a community with low adaptive capacity and high sensitivity is more vulnerable. Vulnerability reduction depends on adaptation policy and strategies. Designing and assessing these strategies require climate vulnerability (CV) measuring. To produce a new CV index, as a main propose of this study, first: The score of exposure factor for two five span years was calculated based on four synoptic stations data (Zabol, Zahedan, Iranshahr and Chabahar). Second: The scores of adaptive capacity and climate sensitivity were determined using all of the country census and yearbook data for 1385 and 1390. Third: Due to the nature and factors of vulnerability, a climate vulnerability index was developed based on the multiplicative-exponential model (CVIMEM). Forth: The index was calculated for the province and sub regions. The result shows, although the Sistan and Baluchistan (SB) adaptation capacity was increased, but because of the increased exposure and sensitivity, this province is 16.3% more vulnerable. Area with very high vulnerability label expanded from 57.5% to 100%, which reflects the spatial expansion of vulnerability over SB. The overall result is that vulnerability reduction needs for accurate and continuous measurement, on the increase adaptation capacity and mitigate climate sensitivity.